2017
DOI: 10.1159/000485082
|View full text |Cite
|
Sign up to set email alerts
|

Catechins Blunt the Effects of oxLDL and its Primary Metabolite Phosphatidylcholine Hydroperoxide on Endothelial Dysfunction Through Inhibition of Oxidative Stress and Restoration of eNOS in Rats

Abstract: Background/Aims: We explored the effects of catechins (decaffeinated green tea extracts containing (–)-epicatechin, (–)-epigallocatechin, (–)-epicatechin gallate and (–)-epigallocatechin gallate) on atherosclerosis risk factors, oxidized low-density lipoprotein (oxLDL) and its primary metabolite, phosphatidylcholine hydroperoxide (PCOOH) induced oxidative injury in cultured endothelial cell line and rats. Methods: We used endothelial cell line and male Wistar rats to determine the effect of catechins on oxLDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In GC/MS and HPLC analysis, we observed that VOS contained several compounds with anti-inflammatory activity such as 4-((1E)-3-Hydroxy-1-propenyl)-2-methoxyphenol [51], methyl palmitate [52], n-hexadecanoic acid [53], sinapyl alcohol [54], phytol [55], linolenic acid [56], stigmast-5-en-3-ol (phytosterols) [57], β-amyrin [58], (+)-catechin [59], (−)-epicatechin [59] and proanthocyanidin [60]. Although various compounds with anti-inflammatory activity were analyzed from VOS, it is necessary to investigate which compounds affect the anti-inflammatory activity of VOS through activation tracing separation.…”
Section: Discussionmentioning
confidence: 99%
“…In GC/MS and HPLC analysis, we observed that VOS contained several compounds with anti-inflammatory activity such as 4-((1E)-3-Hydroxy-1-propenyl)-2-methoxyphenol [51], methyl palmitate [52], n-hexadecanoic acid [53], sinapyl alcohol [54], phytol [55], linolenic acid [56], stigmast-5-en-3-ol (phytosterols) [57], β-amyrin [58], (+)-catechin [59], (−)-epicatechin [59] and proanthocyanidin [60]. Although various compounds with anti-inflammatory activity were analyzed from VOS, it is necessary to investigate which compounds affect the anti-inflammatory activity of VOS through activation tracing separation.…”
Section: Discussionmentioning
confidence: 99%
“…Catechins are known to influence vasodilation, a key factor in maintaining proper endothelial function and preventing atherosclerosis development. Studies conducted in HUVECs, bovine coronary artery endothelial cells (BCAECs), and male Wistar rats have demonstrated that catechins can enhance eNOS expression and NO production, offering protection against endothelial dysfunction and vasoconstriction [ 30 , 34 ]. Catechins also exhibit anti-atherosclerotic properties by influencing cellular aging and apoptosis [ 34 , 141 ].…”
Section: Sirt1 Activators and Atherosclerosismentioning
confidence: 99%
“…These compounds are found in many plants and foods, such as fruits, vegetables, tea, cereals, and wine, and long-term intake is associated with health benefits [ 20 ]. Interesting in vivo (Table 1 ) [ 21 – 31 ], in vitro (Table 2 ) [ 22 24 , 30 , 32 – 35 ], and human (Table 3 ) [ 36 – 39 ] clinical trial studies have shown their effects on atherosclerosis development and risk factors associated with atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ApoE -/mice, catechin consumption has been associated with reduced susceptibility of LDL to oxidation and aggregation and thus to the reduced atherosclerotic lesion area [81]. Recently, in vivo findings show that catechins reduce circulating LDL cholesterol and protect HUVECs against oxidative injury and decrease arterial vasoconstriction through reduction of H 2 O 2 activity and eNOS level restoration [82,83].…”
Section: Flavonoidsmentioning
confidence: 99%